2017
DOI: 10.17129/botsci.747
|View full text |Cite
|
Sign up to set email alerts
|

Screening for root and shoot traits in different wheat species and wild wheat relatives

Abstract: Background: Definitive comparison on root traits of wheat landraces, ancient wheat species and wild wheat relatives are scarce. Those adaptive genetic resources with superior root and shoot traits can be utilized in breeding programs. Questions: Do modern wheats have more superior root and shoot traits than ancient wheat species and wild wheat relatives? Studied species: We performed large-scale screening for significant root and shoot traits of 47 different genotypes including cultivars, lines, landraces, anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
8
2
Order By: Relevance
“…The rooting pattern in wheat species and in hybrids was affected by high shoot biomass, which was remobilized from higher leaf photosynthesis reserves to roots, important for meeting carbon requirements. A previous study of wheat cultivars grown in a mixture of peat and perlite found greater rooting depths in Z31, ranging from 189 to 216.6 cm (mean of two years), in comparison to values of 34.8-116.7 cm in the present study (Akman et al, 2017b).…”
Section: Hierarchical Clusteringcontrasting
confidence: 64%
“…The rooting pattern in wheat species and in hybrids was affected by high shoot biomass, which was remobilized from higher leaf photosynthesis reserves to roots, important for meeting carbon requirements. A previous study of wheat cultivars grown in a mixture of peat and perlite found greater rooting depths in Z31, ranging from 189 to 216.6 cm (mean of two years), in comparison to values of 34.8-116.7 cm in the present study (Akman et al, 2017b).…”
Section: Hierarchical Clusteringcontrasting
confidence: 64%
“…In wheat, root traits have been shown to differ between varieties (e.g., [7,11,12]) and desirable traits are different based on environmental constraints [5]. Plant phenotyping on 36 genotypes chosen along the key steps of evolution in tetraploid wheat from wild emmer to emmer to durum wheat indicates that domestication has changed shoot and root mass and biometric traits [13], although [14] showed that experimental growth conditions such as soil type may affect the extent and direction of the observed changes therefore conclusions are not easy to generalize.…”
Section: Introductionmentioning
confidence: 99%
“…This allows to face dry spells without reducing yield, but at the cost of high water consumption, and is considered an efficient strategy in environments where wheat can rely on in-season rainfall with occasional water shortages, as opposed to water-saving wheat varieties which are more successful in environments where wheat grows on stored water [4]. Nevertheless, in spite of the low harvest index of tall ancient phenotypes in high input conditions, some ancient wheats may provide valuable traits in erratic environment and input due to high plasticity in carbon allocation which results in favorable allometry or root traits under drought [3,12]. Research on root and allocation traits of ancient wheats though is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, many physiological, morphological and architectural plant root traits influence N uptake by plants (Abalos et al., 2019). For example, for root morphological and architectural traits, larger root biomass, root to shoot ratio (RS), root length (RL), specific root length (SRL) (Akman et al., 2017; Bakhshandeh et al., 2016; Corneo et al., 2016; Ehdaie et al., 2010), higher root length density (RLD) (Nakhforoosh et al., 2014; Wang et al., 2016), root surface area (RSA) (Narayanan et al., 2014), and larger amounts of fine roots (Becker et al., 2016; Wang et al., 2016) improve nutrient uptake of plants. Still, due to time‐consuming phenotyping and difficult selection for root traits, breeding programmes historically focused primarily on yield and aboveground plant traits rather than belowground plant characteristics (McGrail et al., 2020; Nevo & Chen, 2010).…”
Section: Introductionmentioning
confidence: 99%